Impact of heart disease on maternal, fetal and neonatal outcomes in a low-resource setting. Issue 10 (10th November 2018) - Beaton, Andrea; Okello, Emmy; Scheel, Amy; DeWyer, Alyssa; Ssembatya, Renny; Baaka, Olivia; Namisanvu, Henrietor; Njeri, Angela; Matovu, Alphons; Namagembe, Imelda; Mccarter, Robert; Carapetis, Jonathan; et al.
Abstract : Background: The burden of pre-existing cardiovascular disease and the contribution to adverse pregnancy outcomes are not robustly quantified, particularly in low-income countries. We aimed to determine both the prevalence of maternal heart disease through active case finding and its attributable risk to adverse pregnancy outcomes. Methods: We conducted a 24-month prospective longitudinal investigation in three Ugandan health centres, using echocardiography for active case finding during antenatal care. Women with and without heart disease were followed to 6 weeks post partum to determine pregnancy outcomes. Prevalence of heart disease was calculated. Per cent attributable risk estimates were generated for maternal, fetal and neonatal mortality. Results: Screening echocardiography was performed in 3506 women. The prevalence of heart disease was 17 per 1000 women (95% CI 13 to 21); 15 per 1000 was rheumatic heart disease. Only 3.4% of women (2/58) had prior diagnosis. Cardiovascular complications occurred in 51% of women with heart disease, most commonly heart failure. Per cent attributable risk of heart disease on maternal mortality was 88.6% in the exposed population and 10.8% in the overall population. Population attributable risk of heart disease on fetal death was 1.1% and 6.0% for neonatal mortality Conclusions: Occult maternal heart disease may be responsible for a substantial proportion of adverse pregnancy outcomes in low-resource settings. Rheumatic heart disease is, by far, the most common condition, urging global prioritisation of this neglected cardiovascular disease.